Neonatal Abstinence Syndrome: Update on Diagnostic and Therapeutic Strategies. Issue 7 (2nd July 2017) - Raffaeli, Genny; Cavallaro, Giacomo; Allegaert, Karel; Wildschut, Enno Diederik; Fumagalli, Monica; Agosti, Massimo; Tibboel, Dick; Mosca, Fabio
Abstract : Substance use among pregnant women is a major public health issue. Both prescription opioid use and illicit opioid abuse have increased dramatically in recent years. Prolonged in utero drug exposure may result in neonatal abstinence syndrome (NAS), an acute multisystemic clinical entity that occurs in the first days of life. This syndrome is caused by abrupt discontinuation of fetal exposure to licit or illicit drugs chronically consumed by the mother during pregnancy and transmitted to the fetus through the placenta. It usually requires prolonged hospitalization and may have long‐term effects. The interplay of many factors contributes to its clinical heterogeneity, and its pathophysiology has not been fully unveiled. The first step in NAS management consists of nonpharmacologic interventions and includes promoting breastfeeding when not contraindicated. If withdrawal signs become severe, pharmacotherapy is needed. The Finnegan scoring system supports care providers across the pharmacotherapy process from initiation through the monitoring phase, until weaning and discontinuation. However, a standardized approach to pharmacotherapy is still lacking. Morphine is usually the first‐line agent to treat NAS. Methadone is a valid option, but its safety profile is not completely known. Phenobarbital, despite its lack of effect on gastrointestinal symptoms and unfavorable pharmacologic features, has been identified as a second‐line agent to be used in infants unresponsive to opiates. Although buprenorphine and clonidine seem promising, their use requires further validation. Long‐term developmental effects of NAS therapy call for more‐comprehensive, longitudinal assessments. In this article, key points for use of recommended therapies are outlined, and directions for future research are suggested.